Compressible metal-organic framework-nanofibrous reinforced chitosan aerogel for efficient removal of Pb(II) ions. (December 2022) - Li, Xiang; Shao, Hong; Ma, Qianli; Yu, Wensheng; Dong, Xiangting
Abstract: Herein, zirconium-based metal-organic-framework/nanofibrous reinforced chitosan (CS) aerogel of UiO-66-NH2 /PANNs/CS aerogel with lightweight, compressible and efficient adsorption properties, was prepared through a facile blending method combining electrospinning, chemical crosslinking and freeze-drying technologies. UiO-66-NH2 /PANNs/CS aerogel inherits large surface area and high porosities from feedstock MOFs, endowing lightweight property. The compressibility of CS aerogel is improved by incorporating polyacrylonitrile (PAN) nanofibers. The structure of UiO-66-NH2 /PANNs/CS aerogel and Pb (II) adsorption experiments are systematically characterized and investigated. UiO-66-NH2 can preserve the micropore and accessibility in the composite aerogels compared with pure powdered forms, making the composite aerogels ideal sorbents for water purification. In the further removing Pb(II) experiments from wastewater, the saturated adsorption capacities of UiO-66-NH2 and UiO-66-NH2 /PANNs/CS aerogel for Pb(II) reach 143.05 and 113.64 mg/g, which are greatly higher than almost all other porous materials. The UiO-66-NH2 /PANNs/CS aerogel also mainly relies on UiO-66-NH2 to adsorb Pb(II). At the same time, the adsorption efficiency of UiO-66-NH2 /PANNs/CS aerogel for Pb(II) is still more than 92.37% after 5 cycles of adsorption-desorption, indicating the excellent reusability. This study provides a general strategy to prepare excellent UiO-66-NH2 /PANNs/CS aerogel with promising practical application potentials in the fields of water treatment. Graphical Abstract: ga1 Highlights: Novel UiO-66-NH2 /PANNs/CS aerogel was prepared with lightweight. The crosslinked composite aerogel is compressible by incorporating PAN nanofibers. Surface area of composite aerogel was increased due to massive loading of UiO-66-NH2 . The adsorption capacity of composite aerogel to Pb (II) was reached to 113.64 mg·g −1 . The UiO-66-NH2 /PANNs/CS aerogel exhibits superior regenerability.